Metabolic remodeling precedes mTORC1-mediated cardiac hypertrophy. (September 2021) - Davogustto, Giovanni E.; Salazar, Rebecca L.; Vasquez, Hernan G.; Karlstaedt, Anja; Dillon, William P.; Guthrie, Patrick H.; Martin, Joseph R.; Vitrac, Heidi; De La Guardia, Gina; Vela, Deborah; Ribas-Latre, Aleix; Baumgartner, Corrine; et al.
Abstract: Rationale: The nutrient sensing mechanistic target of rapamycin complex 1 (mTORC1) and its primary inhibitor, tuberin (TSC2), are cues for the development of cardiac hypertrophy. The phenotype of mTORC1 induced hypertrophy is unknown. Objective: To examine the impact of sustained mTORC1 activation on metabolism, function, and structure of the adult heart. Methods and results: We developed a mouse model of inducible, cardiac-specific sustained mTORC1 activation (mTORC1 iSA ) through deletion of Tsc2 . Prior to hypertrophy, rates of glucose uptake and oxidation, as well as protein and enzymatic activity of glucose 6-phosphate isomerase (GPI) were decreased, while intracellular levels of glucose 6-phosphate (G6P) were increased. Subsequently, hypertrophy developed. Transcript levels of the fetal gene program and pathways of exercise-induced hypertrophy increased, while hypertrophy did not progress to heart failure. We therefore examined the hearts of wild-type mice subjected to voluntary physical activity and observed early changes in GPI, followed by hypertrophy. Rapamycin prevented these changes in both models. Conclusion: Activation of mTORC1 in the adult heart triggers the development of a non-specific form of hypertrophy which is preceded by changes in cardiac glucose metabolism. Graphical abstract: Unlabelled Image Highlights: mTORC1 activation via inducible cardiac-specific TSC2 knockdown results in hypertrophy without contractile dysfunction. mTORC1-induced cardiac hypertrophy is preceded by a decrease of glucose 6-phosphate isomerase levels and activity. Activation of mTORC1 by voluntary exercise is associated with reduced TSC2 phosphorylation at Serine 1387. In animals subjected to vuluntary exercise, changes in glucose 6-phosphate isomerase are present prior to hypertrophy.